Penerapan Terapi Relaksasi Benson Terhadap Tekanan Darah Sistole Pada Lansia Dengan Hipertensi di Kelurahan Bejen Kabupaten Karanganyar - Adelia Qusnul Khotimah; Eska Dwi Prajayanti (Jurnal Medika Nusantara, 2024)
Hypertension is a disease that commonly occurs in the elderly and is more susceptible to complications. The consequences for elderly people with hypertension are heart failure, stroke and kidney failure. According to the World Health Organization (WHO) in 2020, the prevalence of hypertension in the elderly in the world was around 972 million people or 26.4%. Hypertension in the elderly in Wonorejo Hamlet Rw 17 Bejen Village, Karanganyar Regency totaled 83 people. One form of relaxation that can be applied to hypertension sufferers is Benson relaxation therapy. To describe changes in systolic blood pressure due to the application of Benson relaxation therapy in elderly people with hypertension in Bejen Village, Karanganyar Regency. This research used a descriptive design on 2 female respondents aged 60 years and over. After carrying out Benson relaxation therapy which was carried out on 01-07 May 2024 in Bejen Village, Karanganyar Regency with each respondent being given intervention for 7 consecutive days once a day every morning for 10 minutes, the systolic blood pressure in both respondents decreased from grade 2 hypertension to grade 1 hypertension. Application of Benson relaxation therapy can reduce systolic blood pressure in elderly people with hypertension in Bejen Village, Karanganyar Regency.